Effectiveness of Training Program Regarding Gullian Baree Syndrome Maneuver on Pediatric Nurses’ Knowledge and Practices - Amina Mohamed Thabet; Mahmud, Huda Shawky; Eman Hassan; Zahra Ahmed Sayed; Nora Abd- Elhamid Zaki; Naglaa Gamal Eldien Abdelhafez Hariedy (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Guillain-Barre syndrome is an acquired inflammatory polyneuropathy characterized byrapidly progressive symmetrical flaccid limb weakness and a reflexia.Design. A quasi-experimental design was used to guide this study. The study included a sample of 30 nurseswho work at pediatric intensive care and neurology unit in Assuit University Children Hospital.Data were collected using a questionnaire and an observation checklist, used in pre-post testing to measurethe effectiveness of the training program among nurses.Results: The study revealed deficiency in pre-intervention nurses’ knowledge and practices. Statisticallysignificant improvements on knowledge and practices were demonstrated at the post-intervention time forthe studied nurses. Statistically significant relations were shown between knowledge and practices amongstudied nurses.Conclusion: Implementation of the training program significantly improved nurses’ knowledge and practice.More experienced and aged nurses had better knowledge.